Image and Imaging in Philosophy, Science and the Arts. Volume 1. Proceedings of the 33rd International Ludwig Wittgenstein-Symposium in Kirchberg, 2010 - Nemeth, Elisabeth (Publications of the Austrian Ludwig Wittgenstein Society - New Series (N.S.), 2011)
What is an image? How can we describe the experience of looking at images, and how do they become meaningful to us? In what sense are images like or unlike propositions? Participants of the 33rd International Wittgenstein Symposium--philosophers as well as historians of art, science, and literature--provide many stimulating answers. Some of the contributions are dedicated to Wittgenstein's thoughts on images while others testify to the important role notions coined or inspired by Wittgenstein--"seeing as", "picture games" and the dichotomy of "saying and showing"--play in the field of picture theory today. This first volume of the Proceedings of the 2010 conference addresses readers interested in the history and theory of images, and in the philosophy of Wittgenstein.